The Costs of Greece's Fiscal Consolidation - Sebastian Gechert; Ansgar Rannenberg (Vierteljahrshefte zur Wirtschaftsforschung, 2015)
This policy brief reexamines the effects of the Greek austerity experiment on its economy via a counterfactual analysis. We combine the fiscal multipliers from the meta regression analysis in Gechert and Rannenberg (2014) to the fiscal consolidation measures that have been implemented in Greece between 2010 and 2014. We estimate that austerity explains almost the entire collapse of Greek GDP after 2009. This result suggests that-ceteris paribus-, in the absence of austerity, the Greek economy would have entered a prolonged period of stagnation, rather than a depression. At the same time the path of the government debt-to-GDP ratio would have been only somewhat higher. Furthermore, we estimate that if the consolidation would have been postponed until after the recovery of the Greek economy and implemented gradually, almost 80 percent of the cost in terms of lost output could have been avoided. Our results suggest that the period 2010-2014 was the wrong time to implement frontloaded spending cuts due to their strong multipliers in downturns. Implementing only the revenue components of the Greek fiscal consolidation would have strongly reduced the output contraction as compared to the actual path of GDP, but would have been much more effective at lowering the debt-to-GDP ratio than the actual fiscal consolidation. A more cautious consolidation would thus have been in the interest of international creditors as well.
Keywords: E27; E62; H30; 330; Fiscal multiplier; regime dependence; austerity